Research of the RSSR Mechanism with a Variable Rod Length Used in Locking Flat Layer of Construction Lift - Wang Liangwen; Li Quntao; Li Hongpeng; Lou Zhenwei; Zhang Lei; Song Xiaowei (Jixie chuandong)
In a flat layer locking- mechanism of SS type construction lift,a spatial RSSR mechanism with variable rod length is developed,it is used to lock the construction lift flat layer by combining planar sine-mechanism. According to adjust the rod length of RSSR mechanism in terms of the cage opening door angles on construction lift,the output component displacement of sine- mechanism remains unchanged under the different opening angles of cage door to realize the reliable work can be guaranteed through the flat layer locking mechanism. The structure of the mechanism is introduced,the motion model of this combined mechanism is built,the relevant design and computation process is provided,an example is taken to illustrate. A reliable reference for developing similar product is provided through the research work.